A Novel Window into Angiogenesis — Intravital Microscopy in the AV-Loop-Model - Vaghela, Ravikumar; Arkudas, Andreas; Gage, Daniel; Körner, Carolin; von Hörsten, Stephan; Salehi, Sahar; Horch, Raymund E.; Hessenauer, Maximilian (Cells, 2023)
Due to the limitations of current in vivo experimental designs, our comprehensive knowledge of vascular development and its implications for the development of large-scale engineered tissue constructs is very limited. Therefore, the purpose of this study was to develop unique in vivo imaging chambers that allow the live visualization of cellular processes in the arteriovenous (AV) loop model in rats. We have developed two different types of chambers. Chamber A is installed in the skin using the purse sting fixing method, while chamber B is installed subcutaneously under the skin. Both chambers are filled with modified gelatin hydrogel as a matrix. Intravital microscopy (IVM) was performed after the injection of fluorescein isothiocyanate (FITC)-labeled dextran and rhodamine 6G dye. The AV loop was functional for two weeks in chamber A and allowed visualization of the leukocyte trafficking. In chamber B, microvascular development in the AV loop could be examined for 21 days. Quantification of the microvascular outgrowth was performed using Fiji-ImageJ. Overall, by combining these two IVM chambers, we can comprehensively understand vascular development in the AV loop tissue engineering model¯.
CRIS-Team Scopus Importer:2023-02-03
Keywords: arteriovenous loop; GelMA; intravital microscopy; tissue engineering